2020
DOI: 10.4040/jkan.20123
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Empathy among Clinical Nurses in China: A Qualitative Study

Abstract: Purpose: This study aimed to explore the motives of clinical nurses for experiencing empathy with patients and their families based on a self-determination theory framework. Methods: Semi-structured face-to-face interviews with twenty-one nurses at four tertiary hospitals in Anhui, China, were conducted, recorded and transcribed. A content analysis with a directed approach was performed. Results: An analysis of the interview transcripts revealed three categories of empathy motivation: autonomous motivation, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies found high levels of altruism among nursing students. 13,14 Nurses spontaneously show understanding and care to patients and their families because of pure altruism, without expecting anything in return, reflecting the nature of the nursing profession 15 A developed graduate nursing education system has been formed in nations including the United States, the United Kingdom, and Australia. Chinese graduate nursing education started late, and the Master of Science degree in Nursing wasn't established until 2010, which enabled medical universities to quickly establish a curriculum system for nursing graduate education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found high levels of altruism among nursing students. 13,14 Nurses spontaneously show understanding and care to patients and their families because of pure altruism, without expecting anything in return, reflecting the nature of the nursing profession 15 A developed graduate nursing education system has been formed in nations including the United States, the United Kingdom, and Australia. Chinese graduate nursing education started late, and the Master of Science degree in Nursing wasn't established until 2010, which enabled medical universities to quickly establish a curriculum system for nursing graduate education.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found high levels of altruism among nursing students. 13,14 Nurses spontaneously show understanding and care to patients and their families because of pure altruism, without expecting anything in return, reflecting the nature of the nursing profession 15…”
Section: Introductionmentioning
confidence: 99%